Study on well water quality in north-eastern Kelantan / Ahmad Saat ...[et al.] - Saat, Ahmad; Sohari, Rita Rohaizah; Abdul Khalil, Khaniza Hasliza; Hamzah, Zaini; Ahmad Shaberi, Aidawati; Mahasim, Nor Wahida (2006)
In the north-eastern districts of state of Kelantan almost 40% of the populations are still relying on well water for their domestic uses and consumption. Generally, the wells are located within the vicinity of agricultural activities, such as tobacco, paddy, rubber plantations and orchards. Thus. there is possibility that these activities, especially application of fertilizers, may pollute the wells. A study was carried out on thirty wells in the districts of Bachok and Pasir Puteh to determine the well-water quality as well as the nitrate, phosphate, sulphate and chlorine ion contents of the water samples. The sampling was done twice in July and August 2005. Data for salinity, turbidity, temperature. DO, pH , and conductivity were determined in-situ, while minerals contents, BOD and COD were determined in laboratory. Water Quality Index (WQI) of the samples was determined based on the method suggested by Interim Water Quality Standards (INWQS) for Malaysia. In general, WQI in all the wells studied for the two sampling dates fall into class III, slightly polluted category. Based on the INWQS, these classes of water required extensive treatment before being used as public water supply. The study was also extended to the investigation on the presence of coliform bacteria in the water samples.